The influence of user experience and e-service quality on customer satisfaction on Sociolla website users in Indonesia - Fidelia The; Julian Trisnawati; Fitri Widjaja; Nasir Ahmad Zargar (Faculty of Business and Economics, University of Surabaya, 2025)
This study examines how user experience and the quality of electronic services influence customer satisfaction among Indonesian users of the Sociolla website. All Sociolla website users in Indonesia were the focus of this research. Data was analyzed using Structural Equation Modeling (SEM) with SMART PLS 3 software, based on 327 primary data points collected from a questionnaire. The findings reveal a significant positive impact of user experience on e-service quality, e-service quality on customer satisfaction, and user experience directly on customer satisfaction. Moreover, e-service quality acts as a mediator between user experience and customer satisfaction.